2020
DOI: 10.1002/hbm.25219
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reorganization following auditory deprivation predicts cochlear implant performance in postlingually deaf adults

Abstract: Long-term hearing loss in postlingually deaf (PD) adults may lead to brain structural changes that affect the outcomes of cochlear implantation. We studied 94 PD patients who underwent cochlear implantation and 37 patients who were MRIscanned within 2 weeks after the onset of sudden hearing loss and expected with minimal brain structural changes in relation to deafness. Compared with those with sudden hearing loss, we found lower gray matter (GM) probabilities in bilateral thalami, superior, middle, inferior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Given that life expectancy and the exposure to noise are rising, hearing problems will become increasingly prevalent in the ageing population ( Sun et al, 2021 ). Therefore, treatment methods have to be optimised, as hearing loss is an important factor influencing the quality of live (confirmed here with the NCIQ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that life expectancy and the exposure to noise are rising, hearing problems will become increasingly prevalent in the ageing population ( Sun et al, 2021 ). Therefore, treatment methods have to be optimised, as hearing loss is an important factor influencing the quality of live (confirmed here with the NCIQ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported volumetric changes in the insula vary considerably and range from a GM increase in the posterior left insula ( Allen et al, 2008 ) to an overall bilateral GM decrease ( Olulade et al, 2014 ). A recent study reported a GM decrease in the right insula in postlingual deafness ( Sun et al, 2021 ), a finding which was confirmed in a meta-analysis and meta-regression study ( Manno et al, 2021 ). Conflicting results were also reported for the insular WM, going from a bilateral decrease in deaf compared to normal hearing signers ( Olulade et al, 2014 ) to a WM increase in the right insula in SL users (comparison between deaf and normal hearing signers, and normal hearing non-signers) ( Allen et al, 2008 ).…”
Section: Discussionmentioning
confidence: 60%
“…In children, the results were inconsistent, some reporting increases and others decreases in GM in STG. A recent study conducted in a large cohort of 94 postlingually deaf adults, not included in the ALE analysis because of lack of MNI coordinates, found a global GM decrease in the superior, middle and inferior temporal cortices ( Sun et al, 2021 ). This study further showed an interaction between GM changes and duration of deafness: the decrease in the middle temporal cortices was found exclusively in participants who had been deaf for more than 10 years, whereas the decrease in the superior temporal cortices was limited to participants who had been deaf for less than 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the functional connectivity between the thalamus and middle temporal gyrus was previously found to be decreased in SNHL adults (Xu et al, 2019). The cortical thickness of the middle temporal gyrus was found to be increased in postlingually deaf adults (Pereira-Jorge et al, 2018) but decreased in prelingually profound SNHL children (Qu et al, 2020) and postlingually deaf adults (Sun et al, 2021). Thus, we speculated that the functional and structural changes in the middle temporal gyrus in SNHL patients will differ between children and adults, and between prelingually deaf patients and postlingually deaf patients.…”
Section: Hub Distribution Differencesmentioning
confidence: 93%